Metabolic Shifts as the Hallmark of Most Common Diseases: The Quest for the Underlying Unity - Schwartz, Laurent (Int J Mol Sci, 2021)
A hyper-specialization characterizes modern medicine with the consequence of classifying the various diseases of the body into unrelated categories. Such a broad diversification of medicine goes in the opposite direction of physics, which eagerly looks for unification. We argue that unification should also apply to medicine. In accordance with the second principle of thermodynamics, the cell must release its entropy either in the form of heat (catabolism) or biomass (anabolism). There is a decreased flow of entropy outside the body due to an age-related reduction in mitochondrial entropy yield resulting in increased release of entropy in the form of biomass. This shift toward anabolism has been known in oncology as Warburg-effect. The shift toward anabolism has been reported in most diseases. This quest for a single framework is reinforced by the fact that inflammation (also called the immune response) is involved in nearly every disease. This strongly suggests that despite their apparent disparity, there is an underlying unity in the diseases. This also offers guidelines for the repurposing of old drugs.